Procurement Maturity Reimagined: A Conceptual Model for Regional Owned Enterprises (BUMDs) - Sutisna, Nandang; Shazali, Mansor; Suliantoro, Hery (2025)
Procurement plays a strategic role in the governance of Badan Usaha Milik Daerah (BUMD) or Regional-Owned Enterprises, which operate under dual mandates: public accountability and business efficiency. Existing procurement maturity models often fall short in addressing the hybrid nature of BUMDs. This study develops the BUMD Procurement Maturity Model (BPMM) through a conceptual synthesis of 42 public, private, and hybrid models. The BPMM comprises five dimensions—regulatory governance, institutional capacity, human capital development, digital integration, and strategic procurement—each progressing through five maturity levels from reactive to transformative. The model serves as both a diagnostic tool and a roadmap for institutional reform. It enables BUMDs to assess capabilities, address governance gaps, and implement procurement strategies aligned with local regulations and market needs. The BPMM also contributes to procurement theory by introducing a hybrid-specific maturity framework adaptable to decentralized public enterprises.